Concentric Multiple Rings by Droplet Epitaxy: Fabrication and Study of the Morphological Anisotropy - Somaschini C; Bietti S; Fedorov A; Koguchi N; Sanguinetti S (Nanoscale Research Letters, 2010)
Abstract We present the Molecular Beam Epitaxy fabrication of complex GaAs/AlGaAs nanostructures by Droplet Epitaxy, characterized by the presence of concentric multiple rings. We propose an innovative experimental procedure that allows the fabrication of individual portions of the structure, controlling their diameter by only changing the substrate temperature. The obtained nanocrystals show a significant anisotropy between [110] and [1–10] crystallographic directions, which can be ascribed to different activation energies for the Ga atoms migration processes.